2021
DOI: 10.1007/s43545-021-00255-x
|View full text |Cite
|
Sign up to set email alerts
|

Examining the elevated risk of COVID-19 in transgender communities with an intersectional lens

Abstract: COVID-19 has presented unique and unprecedented struggles for all people, yet they tend to be magnified among marginalized communities. Indeed, in the United States, transgender (trans) people experience oppression in many facets of their lives, which places them at an increased risk for both COVID-19 exposure and complications. This oppression can be broadly categorized into two distinct, yet interrelated categories: health disparities (e.g., decreased immune health) and structural barriers (e.g., employment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…4,5 In addition, some evidence shows that transgender and non-binary people are at elevated risk for negative COVID-19 outcomes, but public health data often fails to report data beyond the binary model of gender/sex. 6,7 Studies have shown women use health services more than men, [8][9][10] and emerging research suggests that they may also engage in COVID-19 prevention strategies (e.g., mask-wearing, social distancing, handwashing) more than men. 11 However, acceptance of the COVID-19 vaccine may stray from these typical gender patterns.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 In addition, some evidence shows that transgender and non-binary people are at elevated risk for negative COVID-19 outcomes, but public health data often fails to report data beyond the binary model of gender/sex. 6,7 Studies have shown women use health services more than men, [8][9][10] and emerging research suggests that they may also engage in COVID-19 prevention strategies (e.g., mask-wearing, social distancing, handwashing) more than men. 11 However, acceptance of the COVID-19 vaccine may stray from these typical gender patterns.…”
Section: Introductionmentioning
confidence: 99%
“…14 The review did not examine non-binary gender populations, 14 but research shows COVID-19 may exacerbate structural inequalities for transgender and gender-diverse communities. 7 Other reviews on gender and COVID-19 vaccination are also global in scope, or broadly examine determinants of COVID-19 vaccination, but are not explicitly focused on gender/sex differences. [15][16][17][18][19] Thus, a review focused on gender/sex differences in vaccination in the U.S. population would fill a gap in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have suggested that these stressors have disproportionally impacted the health and well-being of TGNC people (Drabble & Eliason, 2021; Hawke et al, 2021; Woulfe & Wald, 2020). Although the pandemic began to ease in the United States during data collection for Study 2, its various negative impacts on TGNC populations can have long-term consequences (Goldie & Chatterjee, 2021). Given the specific context and stress associated with the pandemic, several confounds may have been introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby nullifying the already existing exaggerated risk of contraction of the disease among trandgenders. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%